Transforming the Poison Effects of Water Vapor into Benefits Over Adjustable Dual Acid Sites for Stable Plasma‐Catalysis - Si Chen; Sibo Zhang; Lu Fang; Yan Yang; Chenyuan Zhu; Xinyi Dai; Zhengjun Gong; Fan Dong (Advanced Science)
Abstract Developing a new strategy to address water vapor poisoning is crucial for catalysts in real‐working conditions. Except for the traditional thinking of resistance enhancement, a reverse idea is proposed herein of utilizing the inevitable H2O, converting it to active ·OH to enhance the overall performance, with the help of O3 and high energy electrons (e*) in plasma. Dual active sites of Lewis acid (Y3+) and Mn on YxMnyOx+2y catalyst promote the co‐adsorption of H2O and O3, and the dissociation of H2O to surface hydroxyl species (*OH). A new OH‐accompanied pathway for O3 decomposition is formed and a new intermediate species (*OOH) with a lower energy barrier (0.77 eV lower than traditional *O22−) is detected, in which e* in plasma can further accelerate its desorption. Thereafter, abundant active ·OH are generated and work for pollutants degradation, achieving 99.78% ethyl acetate (EA) degradation and 97.36% mineralization rate on the surface of YMO (1:2) under humid environment, with excellent long‐term stability. The changed activation site of C─O bond in EA, different by‐products, and reaction pathways are also analyzed. This active species regulation strategy transforms the traditional poison effects of water vapor into great benefits, paving the way for broader catalyst applications free of water vapor.